Typologies of Religiousness/Spirituality: Implications for Health and Well-Being - Park, Nan Sook (Journal of religion and health, 2013)
The purpose of this study was to develop empirically based typologies of religiousness/spirituality (R/S) and to determine whether the typologies were related to health and well-being. The study used a nationally representative sample of adults (N = 1,431). Using latent profile analysis, typologies were derived based on religious service attendance, prayer, positive religious coping, and daily spiritual experiences. Multivariate statistical tests were used to examine cluster differences in health and well-being. A four-class model was identified: highly religious, moderately religious, somewhat religious, and minimally religious or non-religious. The four classes were distinctively different in psychological well-being, in that the highly religious class was most likely to be happy and satisfied with finances and least likely to be psychologically distressed.